A Robust Photocatalytic Hybrid Material Composed of Metal‐Organic Cages and TiO2 for Efficient Visible‐Light‐Driven Hydrogen Evolution. Issue 15 (14th June 2021) - Qin, Su; Lei, Yang; Huang, Jian‐Feng; Xiao, Li‐Min; Liu, Jun‐Min
Abstract: The design of photochemical molecular devices (PMDs) for photocatalytic H2 production from water is a meaningful but challenging subject currently. Herein, a Pd2 L4 type metal‐organic cage (denoted as MOC‐Q2) is designed as a PMD, which consists of two catalytic centers (Pd 2+ ) and four photosensitive ligands (L‐2) with four pyridine anchoring groups. Subsequently, the MOC‐Q2 is combined with TiO2 to form TiO2 ‐MOC‐Q2 hybrid materials with different MOC‐Q2 contents by a facile sol‐gel method, which have micro/mesoporous structures and large surface areas. The optimized TiO2 ‐MOC‐Q2 (6.5 wt%) exhibits high H2 production activity (7.9 mmol g −1  h −1 within 5 h) and excellent durability, giving a TON value of 23477 or 11739 (based on MOC‐Q2 or Pd moles) after recycling for 7 rounds. By contrast, the pure MOC‐Q2 only shows an ordinary photocatalytic H2 production rate (0.84 mmol g −1  h −1 within 5 h) in the homogeneous system. It can be deduced that TiO2 drives the photocatalysis and simultaneously acts as the structure promoter. This study presents a meaningful and distinctive attempt of a new approach for the design and development of MOC‐based heterogeneous photocatalysts. Abstract : A Pd2 L4 type metal‐organic cage (MOC‐Q2) has been synthesized for constructing a photochemical molecular device (PMD). Such a PMD system is creatively immobilized by using a TiO2 substrate to form a robust heterogeneous catalyst for photocatalytic H2 evolution.